Goal-line oracles: Exploring accuracy of wisdom of the crowd for football predictions - Jens Koed Madsen (PLoS ONE, 2025)
Football’s inherent volatility and low-scoring nature present unique challenges for predicting outcomes. This study investigates the efficacy of Wisdom of the Crowd in forecasting football match outcomes as well as expected goals (XG) across a Premier League season. Participants predicted team goal counts, which were then compared to actual expected goals (XG) and match results. Results across 760 team predictions reveal that while Wisdom of the Crowd accurately predicts XG on average, it overestimates ’big-6’ teams and underestimates others, hinting at inherent biases. Notably, however, collective crowd predictions outperform individual estimates consistently, affirming the power of collective intelligence. Furthermore, when tested against betting odds, Wisdom of the Crowd demonstrates limited profitability, indicating its potential as a supplementary rather than sole prediction tool. These findings underscore the nuanced dynamics of football prediction and highlight the utility of collective wisdom in navigating its complexities. Overall, this study contributes insights into crowd prediction dynamics and underscores its potential in football analytics, shedding light on its implications for decision-making and understanding group behaviour in sports forecasting contexts.